2008
DOI: 10.1631/jzus.b0820025
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the chemical characterization and antioxidant properties of acidic polysaccharides from Sargassum fusiforme

Abstract: Abstract:In order to investigate the antioxidant properties of the polysaccharides from the brown alga Sargassum fusiforme, the crude polysaccharides from S. fusiforme (SFPS) were extracted in hot water, and the lipid peroxidation inhibition assay exhibited that SFPS possessed a potential antioxidant activity. Hence, two purely polymeric fractions, SFPS-1 and SFPS-2 were isolated by the column of DEAE (2-diethylaminoethanol)-Sepharose Fast Flow, with their molecular weights of 51.4 and 30.3 kDa determined by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 39 publications
2
22
0
3
Order By: Relevance
“…Polysaccharides can have anti-oxidative properties as well, as reported for oil-in-water emulsions (Chen, Zhang, & Xie, 2004;Mateos-Aparicio, Mateos-Peinado, Jiménez-Escrig, & Rupérez, 2010;Wang et al, 2013;Waraho et al, 2011;Zhou, Hu, Wu, Pan, & Sun, 2008). The anti-oxidative mechanism is due to their metal-chelating activity, free radical scavenging activity, and additionally by the increase in viscosity (Waraho et al, 2011).…”
Section: The Influence Of the Chemical Compositionmentioning
confidence: 78%
See 1 more Smart Citation
“…Polysaccharides can have anti-oxidative properties as well, as reported for oil-in-water emulsions (Chen, Zhang, & Xie, 2004;Mateos-Aparicio, Mateos-Peinado, Jiménez-Escrig, & Rupérez, 2010;Wang et al, 2013;Waraho et al, 2011;Zhou, Hu, Wu, Pan, & Sun, 2008). The anti-oxidative mechanism is due to their metal-chelating activity, free radical scavenging activity, and additionally by the increase in viscosity (Waraho et al, 2011).…”
Section: The Influence Of the Chemical Compositionmentioning
confidence: 78%
“…Since lupin has a higher total dietary fibre content and a higher soluble dietary fibre percentage than soybean (Bähr et al, 2014), the fibre-rich pellet may exhibit even higher antioxidative activity than the fibre-rich material from soybean. Additionally, uronic acids, present in pectin, are positively related with an improved oxidative stability of polysaccharides in tea and brown algae through radical-scavenging (Chen et al, 2004;Zhou et al, 2008). The cell walls of the lupin cotyledon contain a substantial amount of pectins (Guillon & Champ, 2002), and thus an improved oxidative stability of the fibre-rich pellet was to be expected.…”
Section: The Influence Of the Chemical Compositionmentioning
confidence: 99%
“…(2010); Zhou, Hu, Wu, Pan & Sun (2008) and Dou, Meng, Liu, Ren & Guo (2015). These researchers proved that there was a positive correlation between uronic acids content in pectin and its antioxidant activities.…”
Section: Antioxidant Activitymentioning
confidence: 90%
“…This indicated that the existence of uronic acids was the directive factor for the radical scavenging effects of tea polysaccharide conjugates. It also showed a positive correlation between uronic acids and antioxidant capacities in brown alga polysaccharides. The scavenging of the hydroxyl radical was important for antioxidant defence in food systems.…”
Section: Resultsmentioning
confidence: 78%